Financial Analysis of the Enterprise in the Context of Enterprise's Innovations - Kicová, Marianna (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Enterprise's innovations are an important part of strategic enterprise's management. Good and effective management of the enterprise, achievement the required level of performance, as well as long-term prosperity and success is not possible without a detailed knowledge of the enterprise's financial situation. The financial situation reflects the quality and output of the enterprise, the level of its marketing and commercial activities, as well as its innovative activities. Information is essential for proper strategic management. The sources of these information are enterprise's processes that are reflected in the financial statements of the enterprise. The financial analysis of the enterprise is a tool to turn this summary information into the efficient analytical information. The aim of the paper is to analyze the financial situation and financial performance of competing enterprises in the selected sector in the context of enterprise's innovations. The result of the research is the finding that the conclusions of financial analysis have a significant impact on the evaluation of the financial situation and financial performance of the enterprise in terms of understanding the financial health of the enterprise, introducing enterprise's innovations, evaluating market position of the enterprise, establishing a suitable enterprise's strategy and taking actions to improve the financial situation and financial performance of the enterprise.